Plasma Electrolytic Oxidation (PEO) Coatings - Mohedano, Marta; Mingo, Beatriz (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Plasma electrolytic oxidation (PEO), also known as micro-arc oxidation (MAO), functionalizes surfaces, improving the mechanical, thermal, and corrosion performance of metallic substrates, along with other tailored properties (e.g., biocompatibility, catalysis, antibacterial response, self-lubrication, etc.). The extensive field of applications of this technique ranges from structural components, in particular, in the transport sector, to more advanced fields, such as bioengineering. The present Special Issue covers the latest advances in PEO‐coated light alloys for structural (Al, Mg) and biomedical applications (Ti, Mg), with 10 research papers and 1 review from leading research groups around the world.